Movement behavior, habitat selection, and functional responses to habitat availability among four species of wintering waterfowl in California - Overton, Cory T.; Casazza, Michael L. (Frontiers in Ecology and Evolution, 2023)
Habitat selection analyses provide a window into the perceived value of habitats by animals and how those perceptions compare with other animals, change across time, or change in relation to availability (termed: functional responses). Habitat selection analysis and functional responses can be used to develop strategies to avoid habitat limitations, guide habitat management and set attainable conservation goals. GPS relocations of marked animals are the principal data used in habitat selection analysis. The accuracy and frequency with which tracking devices collect data is increasing and may result in non-stationary point processes that result from latent behaviors previously unidentifiable in sparse data. We investigated non-stationary step length distributions and integrated a 2-mixture model of animal movement with step selection analysis to identify patterns of activity among four species of co-occurring waterfowl that winter in the Central Valley of California, United States. We evaluated relative strength of selection and compared functional responses across a range of habitat types for two goose and two dabbling duck species. Goose species (greater white-fronted goose [Anser albifrons] and lesser snow goose [Anser caerulescens caerulescens]) used habitats similarly and displayed similar functional responses with habitat availability. Northern pintail (Anas acuta) displayed functional responses for habitats that provided primary food resources and sanctuary from hunting that were more similar to geese than to mallard (Anas platyrhynchos) which expressed a more generalist pattern of habitat selection. Our results define conditions where food resource competition between geese and ducks could operate which indicate some species may be more impacted than others. Specifically, early season food limitation may manifest more strongly in snow geese due to longer movements and stronger functional response with rice availability. Late season limitations may manifest in northern pintail which remain reliant on rice later but may not be reflected in habitat selection patterns due to a consistent functional response with rice availability. We show that multiple movement processes present in high resolution data can be used to obtain a variety of information about animal behavior and that subsequent step selection analyses may demonstrate unique functional responses relative to alternate habitat selection methods which warrants additional investigation.